2020
DOI: 10.21203/rs.3.rs-46131/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence and Risk Factors of postoperative Dysphagia following Cervical Spine Surgery

Abstract: Background. Dysphagia is a known complication of anterior cervical spine surgery and may be prolonged or occasionally serious. However, the association between posterior cervical spine surgery and the development of dysphagia is rare discussed. Furthermore, the risk factors of postoperative dysphagia are not well understood.Methods. Three hundred and fifty four patients were reviewed in this study, including 172 patients undergoing AC procedure, and 182 patients with PC procedure between June 2007 and May 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…We found that patients in the early phase (≤2 months) of recovery exhibited significant structural and physiologic pharyngeal swallowing impairment as well as a higher incidence of bolus airway invasion on VFSS as compared to healthy controls and patients in the late phase of recovery (> 2 months). Our findings agree with previous investigations that have revealed a decrease in dysphagic symptoms within the first two months post-ACSS with most patients able to return to normal diets shortly after (Leonard & Belafsky, 2011;Kang et al, 2011;Miles et al, 2019;Yu & Tao, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…We found that patients in the early phase (≤2 months) of recovery exhibited significant structural and physiologic pharyngeal swallowing impairment as well as a higher incidence of bolus airway invasion on VFSS as compared to healthy controls and patients in the late phase of recovery (> 2 months). Our findings agree with previous investigations that have revealed a decrease in dysphagic symptoms within the first two months post-ACSS with most patients able to return to normal diets shortly after (Leonard & Belafsky, 2011;Kang et al, 2011;Miles et al, 2019;Yu & Tao, 2020).…”
Section: Discussionsupporting
confidence: 93%